MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI KEGIATAN SENAM FANTASI DI KELAS B1 TK ISTIQOMAH BAGANSIAPIAPI - Juliana, Juliana; Zulkifli N, Zulkifli N; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Learning activities conducted in kindergarten Istiqomah only considers the activities of reading, writing, and arithmetic are important so that the child's gross motor skills are still low it can be seen from the attitude of the child's behavior was not interested and less active in participating in learning gross motor skills. The study goal was to determine through fantasy gymnastics can look at the ability of children to improve gross motor skills, to improve gross motor skills of children and measure how high the increase in children before and after treatment classroom action research, and to find creative ways to make learning fun particularly through gymnastics fantasy. The method used is classroom action research, the research was conducted in May 2015. The number of children in this study were 15 people composed of 7 boys and 8 girls. Data collection technique used observation sheets, based on the data of the percentage increase in the first cycle is 36.02% and the increase in cycle II reached 63.65% of all the data it can be concluded that with the activities of gymnastics fantasy can improve gross motor skills in children 5-6 years old in kindergarten Istiqomah Bagansiapiapi.Keyword : Rough Motoric capabilities , Gymnastics Fantasy